Company investments in the context of financial strategies - Šmejkal, Antonín; Novotná, Martina; Volek, Tomáš (Publishing House of Wroclaw University of Economics and Business, 2022)
This paper is focused on the determination of type of financial strategy to company investment. The analysis traces which financial strategies are preferred by companies from industries classified according to technological intensiveness. The study used data from 7,095 Czech enterprises during the 2014-2018 period. The typology of strategies was based on dynamic criteria created by combining indices of financial ratios. This study confirmed that management do not strictly prefer a conservative or aggressive investment strategy. A quarter of investment companies are rather inclined towards a strategy with conservative elements regarding the area of financing and aggressive elements regarding the golden rule of investing (Strategy B). One-third of the companies practise risky investment (long-term assets grow faster than sales). The contribution of this paper is an extension of investment theory by the typology of financial strategies of investing companies, which can be useful in making future investor decisions, for creators of subsidy policies and financial institutions providing financing for company investments.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 163-185
Keywords: company investments; fixed assets; criteria; business investment strategy